Analisis Penerapan Pajak Penghasilan Usaha Mikro Kecil dan Menengah: Pada KPP Pratama Makassar Selatan dan Makassar Utara - Sormin, Barita; Rahim, Syamsuri (STIEM BONGAYA, 2019)
This research aimed to: (1) To obtain and analyse application of Indonesian Government Act No. 23 of 2018 about increasing level of Micro Small and Medium Enterprises taxpayers who apply in South Makassar and North Makassar Tax Office, (2) to obtain and analyse application of Indonesian Government Act No. 23 of 2018 about contributed Micro Small and Medium Enterprises income taxes related to collection of income taxes Article 4 Section 2 in South Makassar and North Makassar Tax Office. Analysis method used in this research is descriptive analysis to describe increasing number of taxpayers before and after after application of Government Act No.23 of 2018 about collection of income taxes Article 4 Section 2. This research used descriptive analysis method with interactive model. Research shown that: (1) in South Makassar Tax Office, after application of Government Act No.23, shown increasing number of Micro Small and Medium Enterprises taxpayers for 79,61%, in the other hand, in North Makassar Tax Office, after application of Government Act No.23, shown decreasing number of Micro Small and Medium Enterprises taxpayers for -2,44%. (2) in South Makassar Tax Office, average collection of income taxes Article 4 Section 2, after 6 months since applying Government Act No. 23 of 2018, is 10,49% with the low criteria, and in North Makassar Tax Office, average collection of income taxes Article 4 Section 2, after 6 months since applying Government Act No. 23 of 2018, is 17,85% with the low criteria. In the future, government especially South Makassar and North Makassar Tax Office needs to be active and keen for holding personal socialization to the taxpayers.